Effects of Delayed Hip Fracture Surgery on Severely Ill Patients: Defining the Time to Medical Optimization. Issue 5 (May 2023) - Darbandi, Aria Darius; Saadat, Ghulam H.; Alsoof, Daniel; Rebic, Ante; Siddiqi, Ahmed; Butler, Bennet A.; Bokhari, Faran
Background: Patients with multiple comorbidities often have delayed hip fracture surgery due to medical optimization. The goal of this study is to identify the allowable time for medical optimization in severely ill hip fracture patients. Methods: The 2016-2019 NSQIP database was used to identify patients over age 60 with ASA classification scores 3 and 4 for severe and life-threatening systemic diseases. Patients were divided into immediate (<24 hours), early (24-48 hours), or late (>48 hours) groups based on time to surgery (TTS). Risk-adjusted multivariable logistic regressions were conducted to compare relationships between 30-day postoperative outcomes and TTS. Results: 43, 071 hip fracture cases were analyzed for the purposes of this study. Compared to patients who underwent surgery immediately, patients who had surgeries between 24 and 48 hours were associated with higher rates of pneumonia (OR 1.357, CI 1.194-1.542), UTIs (OR 1.155, CI 1.000-1.224), readmission (OR 1.136, CI 1.041-1.240), postoperative LOS beyond 6 days (OR 1.249, CI 1.165-1.340), and mortality (OR 1.205, CI 1.084-1.338). Patients with surgeries delayed beyond 48 hours were associated with higher rates of CVA (OR 1.542, CI 1.048-2.269), pneumonia (OR 1.886, CI 1.611-2.209), UTIs (OR 1.546, CI 1.283-1.861), readmission (OR 1.212, CI 1.074-1.366), postoperative LOS beyond 6 days (OR 1.829, CI 1.670-2.003), and mortality (OR 1.475, CI 1.286-1.693) compared to patients with immediate surgery. Discussion: Severely ill patients with the hip fracture may have a 24-hour window for medical optimization. Hip fracture surgery performed beyond 48 hours is associated with higher complication rates and mortality among those who are severely ill. Further prospective studies are warranted to examine the effects of early surgical intervention among severely ill patients.